Is there a relationship between intrapersonal, personal hygiene, and physical environment with incidence of scabies? - Iin Indah sari; Emmi Bujawati; Sukfitrianty Syahrir; Nildawati Amir; Munawir Amansyah (CORE JOURNAL, 2020)
Scabies is one of the most common dermatological problems and affects about 200 million people each year around the world (WHO, 2019). This study aims to see the relationship between intrapersonal, personal hygiene and the physical environment on the incidence of scabies at the Sultan Hasanuddin Islamic Boarding School. This is a quantitative research with an observational analytic approach with a case control design. The sampling technique used was exhaustive sampling (80 students). Chi-Square test results for the interpersonal contact variable was that there was a relationship between changing prayer equipment (p value = 0.000) and the incidence of scabies, th¬ere was no relationship between changing toiletries (p value = 0.115), sleeping huddled (p value = 0.769) to the scabies¬¬¬¬¬¬. For the personal hygiene variables, there was no relationship between bathing habits and the incidence of scabies and there was a relationship between nail cutting habits (p value = 0.004) and changing underwear (p value = 0.000). For the physical environment variables, there was a relationship between lighting (p value = 0.005) humidity (p value = 0.002) on the incidence of scabies and there was no relationship between the physical quality of water and the scabies. It is hoped that there will be efforts to improve the personal hygiene, intrapersonal and sanitation behavior of each student. The results suggest that there is a need for policies in the form of sanctions or rewards for students who can practice intrapersonal, personal hygiene and good environment